Understanding Multiculturalism Education from Indonesia, Singapore, Malaysia, and Thailand - Yuyun Elizabeth Patras; Rais Hidayat; Arifin Maksum; Nina Nurhasanah (Kelola: Jurnal Manajemen Pendidikan, 2022)
Every nation faces increasingly complex challenges. Differences every day meet us. The purpose of this study is to learn from the implementation of multicultural education in four countries. This study uses a qualitative approach with content analysis techniques. The data source comes from 12 English articles obtained from scopus.com with the keywords "Multicultural Indonesia", "Multicultural Singapore", "Multicultural Malaysia", and "Multicultural Thailand". The findings of this study are that multicultural implementation can be carried out through policies and policy practices that must be consistent; the use of real multiculturalism practices; the use of universal values of culture and religion that exist in their respective societies; the use of multicultural music, and the use of the Education curriculum. The results of this study can be used for discussion on the issue of more effective multicultural implementation